2022
DOI: 10.1186/s12939-022-01676-7
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative modelling of social determinants of health using group model building: the case of debt, poverty, and health

Abstract: Background Social determinants of health (SDoH) are known to have a large impact on health outcomes, but their effects are difficult to make visible. They are part of complex systems of variables largely indirect effects on multiple levels, constituting so-called wicked problems. This study describes a participatory approach using group model building (GMB) with stakeholders, in order to develop a qualitative causal model of the health effects of SDoH, taking poverty and debt in the Dutch city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…but also facilitates equitable and social learning processes among stakeholders. 25,27,28,30,34,[36][37][38][39][40][41] Causal loop diagrams are compelling because they offer the unique capability of conveying complex information effectively and parsimoniously and may also be more engaging and interesting than traditional graphs and charts. 37 The act of engaging in visual storytelling by building CLDs helps stakeholders understand the "potential for nonlinear relationships between contributing factors and unanticipated emergent behavior of complex systems," 38(p2) which allows for increased ability to identify leverage points for intervention that may not otherwise be obvious.…”
Section: S13mentioning
confidence: 99%
See 4 more Smart Citations
“…but also facilitates equitable and social learning processes among stakeholders. 25,27,28,30,34,[36][37][38][39][40][41] Causal loop diagrams are compelling because they offer the unique capability of conveying complex information effectively and parsimoniously and may also be more engaging and interesting than traditional graphs and charts. 37 The act of engaging in visual storytelling by building CLDs helps stakeholders understand the "potential for nonlinear relationships between contributing factors and unanticipated emergent behavior of complex systems," 38(p2) which allows for increased ability to identify leverage points for intervention that may not otherwise be obvious.…”
Section: S13mentioning
confidence: 99%
“…29,42,61 Subtheme 1.4: Enhanced research and community trust Many articles reported on the ability of PSD methods to enhance relationships between research institutions and community partners. 30,38,40,44 The collaboration, engagement, and group-based participation involved in engaging in PSD strengthen trust and relations between researchers and community partners. 30,38,40,44 This phenomenon itself acts as a feedback loop, as increased trust in research institutions may inspire community partners to wish to engage in future PSD research, which then produces more capacity to sustain change from communitybased interventions.…”
Section: Family and Community Healthmentioning
confidence: 99%
See 3 more Smart Citations